Risk Factor Analysis of Overnutrition Among Elementary School Children in Pekanbaru: An Urban-rural Perspective - Arfianti, Arfianti (UI Scholars Hub, 2019)
The prevalence of childhood overnutrition is increasing in many parts of the world including Indonesia. National basic health research (RISKESDAS) 2010 showed that over-nutrition in urban children (10.4%) was greater than in rural areas (8.1%). The purpose of this study was to analyse risk factors for overnutrition on elementary students in urban and rural areas in Pekanbaru. This was an observasional analytical study with cross-sectional design. This study involved 137 urban and 113 rural students from six elementary schools in Pekanbaru recruited by quota sampling technique. This study was conducted between April-May 2018. The results showed that the proportions of overweight and obesity in urban Pekanbaru were 16.1% and 16.8% respectively, while in rural areas were 12.4% and 9.7%, respectively. Furthermore, outdoor activity and snacking habit were significant contributors of childhood overnutrition in urban area whereas frequency of main meal was associated with childhood overnutrition in rural area. In conclusion, there was no difference in the incidence of overnutrition among elementary students in urban and rural areas in Pekanbaru. This study indicated that obesity risk factors may be different between urban and rural areas in Pekanbaru.